Pengembangan Prototype Figma Untuk Sistem Point Of Sales (POS) Menggunakan Metode Design Thinking - Kevin Almando Ronovan; Calvin Jonathan; Rio Leonardi; Elvis Sastra Ompusunggu (Jurnal Sistem Komputer dan Informatika (JSON), 2025)
The increasing use of technology in retail operations emphasizes the importance of efficient Point of Sales (POS) systems to manage transactions, inventory, and financial reporting in real-time. Although previous research has used the Figma method for UI/UX design, there are still gaps in understanding user needs and the application of theoretical design approaches such as Design Thinking. This research aims to develop a Figma-based POS prototype by applying five stages of Design Thinking: Empathize, Define, Ideate, Prototype, and Test, to ensure user-centered problem-solving and iterative design improvement. Through this approach, the study resulted in an intuitive and efficient POS prototype, addressing challenges identified in previous studies, such as limitations in user engagement and lack of iterative validation.